Interaction of Policy Actors in Online Learning Implementation - Intan Intan Anggraeny; Mas Roro Lilik Ekowanti; M Husni Tamrin (Journal of Governance and Public Policy, 2021)
This study aims to explain and describe the interaction of policy actors in the implementation of online learning. This study uses a qualitative research method with a descriptive case study approach. Data collection techniques in this study are through observation, documentation, and interviews. The instruments in this study were: a) the researcher himself, b) interview guidelines, c) supporting tools in the form of books, pens, and d) related documents. The results showed that actor interaction can occur if there is communication between implementing actors. Communication in the implementation of online learning can be seen in the accuracy or accuracy of communication and consistency of communication regarding online learning information from the principal to the teacher and finally to students and parents. Interaction between actors, namely principals, teachers, students, and parents in the implementation of online learning has not been carried out effectively. This is because the interaction between implementing actors is unresponsive to one party, namely students and parents. Apart from that, giving complicated and difficult assignments by the teacher, which makes it difficult for students and parents to understand, is also a factor in the existence of negligence or delay